Periscope of Ideas Selective Criteria for the Application of Restorative Justice in Corruption Crimes - Wangga, Maria Silvya E.; Ahmad, Nadzriah; Puluhulawa, Jufryanto; Swarianata, Vifi (Journal of Indonesian Legal Studies, 2024)
This article applies the theory of restorative justice to the analysis of state losses resulting from corrupt activities. This study employs socio-legal research, which is a type of normative legal research that is dependent on values and facts. The study's findings revealed that two (2) points of view are based on the fundamental notion that restorative justice can compensate the state for damages incurred through acts of corruption. First, in order to make up for the losses sustained by the state as a result of corrupt criminal acts, law enforcement must be centered around the idea of restorative justice. Secondly, the fact that the Constitutional Court's ruling Number 25-PUU-XIV-2016 eliminated the word "may" from Article 2 paragraph (1) and Article 3 of Law Number 20 Year 2001 in combination with Law Number 31 Year 1999 for the Eradication of Corruption remains a reality. In order to ensure that substantive justice in the application of restorative justice does not clash with current laws and regulations and is administered with chosen criteria, the A quo ruling nullifies Article 4 of the Corruption Crime Eradication Law.